Five-Year Outcomes Prospective Study of Two First-Generation Trabecular Micro-Bypass Stents (iStent®) in Open-Angle Glaucoma. (1st February 2021) - Saheb, Hady; Donnenfeld, Eric D.; Solomon, Kerry D.; Voskanyan, Lilit; Chang, David F.; Samuelson, Thomas W.; Ahmed, Iqbal Ike K; Katz, L Jay
ABSTRACT: Purpose: To assess 5-year effectiveness and safety of 2 iStent® trabecular micro-bypass stents in eyes with open-angle glaucoma (OAG) not controlled on 1 medication. Materials and Methods: This prospective, interventional, single-arm, multi-surgeon study (NCT #1252862, clinicaltrials.gov) enrolled eyes with OAG, preoperative intraocular pressure (IOP) of 18–30 mmHg on 1 ocular hypotensive medication, and 22–38 mmHg after medication washout. Eyes underwent standalone implantation of 2 iStent devices and were followed through 60 months postoperatively. Efficacy was quantified by mean diurnal IOP and medication usage. Efficacy endpoints included the proportion of eyes with ≥20% IOP reduction versus baseline unmedicated IOP (primary efficacy), and the proportion of eyes with IOP ≤18 mmHg (secondary efficacy) without medication or secondary glaucoma surgery. Safety parameters included visual acuity, cup-to-disc ratio, visual field, and complications and adverse events. Results: Preoperative mean IOP on 1 medication was 20.6 ± 2.0 mmHg and post-washout unmedicated IOP was 24.1 ± 1.4 mmHg (n = 39). At 5 years postoperative, medication-free mean diurnal IOP reduced to 14.5 ± 2.2 mmHg, constituting a 40% decrease versus preoperative washed-out IOP ( p < .0001). In addition, this 5-year medication-free IOP constituted a 30% decrease versus preoperative IOP on 1 medication ( p < .0001). At Month 60, 89.7% (26/29) of eyes achieved the primary efficacy endpoint of ≥20% IOP reduction versus baseline unmedicated IOP, and 86.2% (25/29) of eyes achieved the secondary efficacy endpoint of IOP ≤18 mmHg, without medication or secondary glaucoma surgery. Throughout follow-up, 89.7–91.3% of eyes were on no medications. Favorable safety included no secondary glaucoma surgeries, minimal adverse events, and stable visual acuity, cup-to-disc ratio, and visual fields through 5 years postoperative. Conclusions: This prospective interventional study demonstrates persistent 5-year reductions in IOP and freedom from medications, together with favorable safety, following implantation of 2 first-generation trabecular micro-bypass stents in eyes with OAG on 1 preoperative medication.